SAT0217 Identification of distinct disease activity trajectories in patients with rheumatoid arthritis receiving tofacitinib over 12 months. (12th June 2018) - Bykerk, V. P.; van Vollenhoven, R.; Connell, C.; Gruben, D.; Fallon, L.; Woolcott, J.; Keystone, E.
Abstract : Background: Persistence of active disease in patients (pts) with rheumatoid arthritis (RA) is highly variable following treatment initiation. One possible explanation is the existence of distinct disease activity/response trajectories influenced by baseline variables, such as sociodemographics, disease characteristics and health status. 1 Objectives: To identify distinct disease activity trajectories over 12 months and distinguishing baseline factors using pooled data from 3 randomised, controlled Phase 3 (P3) studies of tofacitinib 5 mg twice daily (BID) in pts with active RA who were inadequate responders (IR) to conventional synthetic (cs)DMARDs, with or without prior biologic (b)DMARDs (NCT00847613, NCT00856544 and NCT00853385 ). Methods: Disease Activity Score in 28 joints, erythrocyte sedimentation rate (DAS28–4[ESR]) data from 3 P3 studies were pooled. A group-based trajectory modelling strategy was applied to find unique longitudinal groups of pts with similar disease activity over time. 2 Trajectories were latent models, fit as polynomials. The number of groups and polynomial degree of each group were specified and fit for all combinations of up to 6 groups and up to a 4th degree polynomial; a best-fit model was chosen using Bayesian information criteria. Results: csDMARD-IR/bDMARD-naïve pts (n=677) were separated into 5 unique disease activity trajectories (figure 1); csDMARD-IR pts who received prior bDMARDs (n=149) were separated into 4 trajectories (not shown). In the bDMARD-naïve pts, Group 5 (3.8%) had the highest predicted baseline DAS (7.3) with minimal improvement (6.4) at Month 12; Group 4 (26.7%) had baseline DAS 7.0, improving to DAS 5.0 at Month 12; Groups 2 (30.4%) and 3 (36.6%) had baseline DAS 5.9 and 6.2, respectively, leading to low DAS (2.9) and moderate DAS (3.9), respectively, at Month 12; Group 1 (2.4%) had the lowest baseline DAS of 4.3, improving to remission (DAS 2.1) at Month 12 (figure 1). The 4 trajectories in csDMARD-IR pts who received prior bDMARDs were similar to Groups 2–5 in bDMARD-naïve pts. While baseline demographics were generally similar between bDMARD-naïve groups, there were statistically significant differences in baseline disease activity measures and pt-relevant outcomes between groups. Conclusions: It was possible to identify heterogeneous phenotypic subgroups as distinct disease activity trajectories in csDMARD-IR pts treated with tofacitinib. The groups were characterised by differences in disease activity and pt-relevant outcomes, including baseline pain and physical function. Very high disease activity may limit pts' ability to achieve low disease activity. The identification of distinct trajectory groups could be used to develop personalised treatment optimisation algorithms incorporating clinical and molecular phenotypes. References: [1]Barnabe C, et al. PLoS One2015;10:e0135327. [2]Nagin DS. In: Handbook of Quantitative Criminology. New York, NY. Springer 2010:53–67. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by R Knight of CMC and funded by Pfizer Inc. Disclosure of Interest: V. Bykerk Grant/research support from: Amgen, BMS, Genentech, UCB, Consultant for: AbbVie, Amgen, BMS, Gilead, Pfizer Inc, Sanofi-Regeneron, UCB, R. van Vollenhoven Grant/research support from: AbbVie, Amgen, BMS, GSK, Pfizer Inc, Roche, UCB, Consultant for: AbbVie, AstraZeneca, Biotest, BMS, Celgene, Crescendo, Eli Lilly, GSK, Janssen, Merck, Novartis, Pfizer Inc, Roche, UCB, Vertex, C. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Keystone Grant/research support from: AbbVie, Amgen, BMS, Eli Lilly, Pfizer Inc, Roche, Consultant for: AbbVie, Amgen, BMS, Eli Lilly, Pfizer Inc, Roche